IL-17 in Rheumatoid Arthritis and Precision Medicine: From Synovitis Expression to Circulating Bioactive Levels - Robert, Marie; Miossec, Pierre (Frontiers in Medicine, 2019)
Interleukin (IL)-17A has a direct contribution in early induction and late chronic stages of various inflammatory diseases. In vitro and in vivo experiments have first characterized its local effect on different cell types and then its systemic effects. For instance, IL-17 axis is now identified as a key driver of psoriasis through its effects on keratinocytes. Similar observations apply for rheumatoid arthritis (RA) where IL-17A triggers changes in the synovium that lead to synovitis and maintain local inflammation. These results have prompted the development of biologics to target this cytokine. However, while convincing studies are reported on the efficacy of IL-17 inhibitors in psoriasis, there are conflicting results in RA. Patient heterogeneity but also the involvement of mediators that regulate IL-17 function may explain these results. Therefore, new tools and concepts are required to identify patients that could benefit from these IL-17 targeted therapies in RA and the development of predictive biomarkers of response has started with the emergence of various bioassays. Current strategies are also focusing on synovial biopsies that may be used to stratify patients. From local to systemic levels, new approaches are developing and move the field of RA management into the era of precision medicine.